Analysis of Gas Nitriding Characteristics under Different Cold Hardening and Nitriding Pressure Conditions for Low-Carbon Low-Alloy Steel - Zhou, Z A.; Fu, W.T.; Zhang, R.H.; Qi, J.J.; Jin, G.F.; Wang, Z.H.; Sun, S.H. (Проблемы прочности, 2018)
A new approach to quick preparation of a nitrided case for low-carbon low-alloy steels was proposed. It is based on cold hardening and pressurized gas nitriding. The microstructure, surface hardness, thickness, and corrosion resistance of the nitrided layer on low-carbon low-alloy steel (20CrMnTi) were investigated after the nitriding at 510°C for 5 h under different cold rolling reduction (0–60% CR) and nitriding pressure (1–5 atm).